Quality Assurance of Higher Education in the 5.0 Era: A Systematic Literature Review Identifying Current Trends and Future Prospects - Adzidzah, Nur; Yudiawan, Agus (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
Quality assurance of higher education (QAHE) is a crucial issue in facing the challenges of the Society 5.0 era, where the integration of advanced technology and humanities is the main focus. This systematic literature review analyzes current trends and prospects of QAHE in the 5.0 era. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, we identify, filter, and analyze scientific articles from databases such as Scopus, Web of Science, and Google Scholar published between 2020 and 2025. The results show that the QAHE trend in the 5.0 era has shifted from a traditional approach that focuses on administrative compliance to a more holistic and adaptive paradigm. Key findings include: (1) the use of artificial intelligence and big data analytics for data-driven decision-making; (2) a shift in focus from input-output to outcomes-based education that emphasizes the relevance of graduates to industry needs; (3) the adoption of agile approaches and flexible curriculum design; and (4) an emphasis on cross-cultural competencies and non-technical skills such as creativity, collaboration, and ethics. The study concludes that QAHE in the 5.0 era demands fundamental reforms, where collaboration between academia, industry, and government is key to creating a resilient and relevant education ecosystem. Prospects indicate deeper integration between technology and the humanities, shaping a more personalized, adaptive, and sustainability-oriented model of QAHE.